Vegetation Density Analysis in Padalarang Bandung Regency Using NDVI Method on Landsat 8 Satellite - Ratna Widyaningtyas; Mini Ambarwati Kusuma Dewi; Maulyda Shofa Azizia; Hashfi Hawali Abdul Matin (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Vegetation is an important component in an ecosystem. Padalarang Sub-District is a sub-district in West Bandung Regency with the smallest area but the most densely populated among other sub-districts in West Bandung, with a density of 3,478 people km2. The purpose of this research is to analyze the level of vegetation density using the Normalized Difference Vegetation Index (NDVI) technique as a consideration, especially for the government regarding development program arrangements. The method used was Landsat 8 image interpretation with NDVI, and the results will be classified according to the classification of vegetation density used. As a result, the density of vegetation has decreased from 2013 to 2021, area of non-vegetation and sparse vegetation land indicates, increasing by 5.3% and 4.51%, respectively. In the classification of fairly dense, dense, and very dense vegetation, density decreased by 4.39%, 4.86%, and 0.55%, respectively, which has resulted in reduced green areas becoming built-up areas along with the development of the number and mobility of the population. It is necessary to increase the amount of vegetation and stipulate development regulations that take into account the existence of vegetation as a support for ecological functions.